Penaruh Ventilasi Kemasan Kotak Karton Gelombang Untuk Buah Manggis - Budi Utami; Hendartini Hendartini (Jurnal Kimia dan Kemasan, 1999)
Corrugated boxes as a transport packaging can decrease the damage of the contains during transportation. The transport packaging for fresh fruit has to be provided by ventilation. However the percentage of the ventilation candecrease the physical properties/the strength of the corrugated boxes it self. Experiment has been carried out to determine the percentage of the ventilation of the corrugated boxes needed for fruit of manggistan. The type of corrugated boxes is Regular Slotted Container (RSC) with inner dimension 300 x 180 x 110 mm and 2, 5 kg by weight. The transport simulation test showed that the optimum percentage of the ventilation is 5 % with the self live of 8 days.